QAShQADARYO VILOYATIDAGI AHOLINING HAZM QILISh ORGANLARI KASALLIKLARIGA ChALINIShI: IQTISODIY GEOGRAFIK JIHATLAR, EKOLOGIK TA’SIRLAR VA TIBBIY PROFILAKTIKA - Fayzullayev, M.A.; Xujamova, S.B. (SCIENCE and SOCIETY, 2025)
This article analyzes the incidence of digestive diseases among the population of Kashkadarya region from the perspective of economic and geographical aspects, ecological factors and the impact of medical preventive measures. The climatic conditions of the region, the state of use of natural resources, the negative impact of industrial enterprises on the environment and the level of environmental pollution were studied as the main factors affecting health indicators. Proposals were put forward to pay attention to the quality of food products, drinking water hygiene and improve the sanitary and epidemiological situation of the population. Also, recommendations were given on preventive measures against the spread of digestive system diseases, including the promotion of a healthy lifestyle, regular medical examinations and improvement of the ecological environment.
Keywords: digestive system diseases; economic geographical factors; environmental impact; health care; medical prevention; ecological environment; sanitary and hygienic conditions; healthy lifestyle